PATUN DALAM BUDAYA REJANG SEKAYUN KABUPATEN BENGKULU TENGAH - Yulyam Farida (Universitas Bengkulu, 2017)
This research is to describe “Patun” in Rejang Sekayun Culture of Center Of Bengkulu Regency. It researched according to direcpion is ucer the use and patun function. Menthod uced in this research is sastra approach. Datas analyced acchording who is tuturan patun Rejang Sekayun of center of Bengkulu ucer, how to use tuturan paun in Rejang Sekayun Center Of Bengkulu Regency? And tuturan patun social function in Rejang Sekayun culture in center of Bengkulu Rejang? From the result of research tound by researcher is patun Rejang Sekayun of center Bengkulu user consist or: (1) patun user by lower social level people to usual people, (2) patun user by lower social level people to top social people, (3) patun user by old people to the youger, (4) patun user by youger to older people. While the uses ol of patun in Rejang Sekayun of center Bengkulu Regency consist or (1) patun of youfh, (2) patun of child, (3) patun pf old people. From patun social function consist of (1) patun function youft relationship, (2) patun function of communication side, elemend and whishes, and (3) patun function of enterrainsmen, while for patun function of related with people’s believes one not found.Kata Kunci: dialog, patun, dan Rejang culture